Efficacy and immunogenicity of novel erythropoietic agents and conventional rhEPO in rats with renal insufficiency - Tillmann, Hanns-Christian; Kuhn, Bernhard; Kränzlin, Bettina; Sadick, Maliha; Gross, J.; Gretz, Norbert; Pill, Johannes (Kidney international, 2006)
Recombinant human erythropoietin (rhEPO) is used to treat anemia in chronic renal insufficiency. Erythropoietin (EPO) immunogenicity can lead to EPO-resistant anemia. Conjugating proteins with polyethylene glycol (PEG) can prolong elimination half-life and diminish protein immunogenicity. We investigated the efficacy of new erythropoietic agents, synthesized by single (Ro 50-3821) and multiple (MIX) integrations of PEG and succinimidyl butanoic acid with rhEPO, in rats with chronic renal insufficiency. Sprague-Dawley rats with surgically induced renal insufficiency received Ro 50-3821 or MIX subcutaneously (s.c.) over 4-12 weeks compared to rhEPO and NaCl. Hemoglobin and antibody levels served as primary efficacy and safety variables. Dosing intervals and dose-response characteristics were investigated. Ro 50-3821 (2.5 μg/kg once weekly) increased hemoglobin levels by 7 g/dl after 4 weeks compared to 1 g/dl in NaCl controls (P<0.05). MIX (2.5 μg/kg once weekly) and rhEPO (0.25 μg/kg three times weekly) increased hemoglobin levels by 3 g/dl. Ro 50-3821 administered for 12 weeks (0.75 μg/kg once weekly) increased hemoglobin levels (from 13 to 19 g/dl) more effectively than rhEPO (0.75 μg/kg once weekly, decline from 13 to 11 g/dl, P<0.05). No antibodies against Ro 50-3821 were detected after 12 weeks of treatment. Antibodies against rhEPO were seen in 69% of animals (P<0.00001). Ro 50-3821 increased hemoglobin levels with once weekly s.c. dosing. Multiple pegylated EPO is less effective. In rats, rhEPO failed to increase hemoglobin levels with once weekly long-term dosing. Antibody formation following rhEPO may explain this finding. Therefore, Ro 50-3821 may provide important clinical advantages compared to unpegylated EPO. It can be administered in longer dosing intervals and has a lower risk of unfavorable immunological responses.